2012
DOI: 10.1021/nn302422x
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Atomic and Electronic Heterostructures of Single-Layer MoS2

Abstract: Nanoscale heterostructures with quantum dots, nanowires, and nanosheets have opened up new routes toward advanced functionalities and implementation of novel electronic and photonic devices in reduced dimensions. Coherent and passivated heterointerfaces between electronically dissimilar materials can be typically achieved through composition or doping modulation as in GaAs/AlGaAs and Si/NiSi or heteroepitaxy of lattice matched but chemically distinct compounds. Here we report that single layers of chemically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

72
855
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 871 publications
(930 citation statements)
references
References 38 publications
72
855
0
3
Order By: Relevance
“…1. The 1T 0 phase is observed in WTe 2 under ambient conditions 17 , MoTe 2 at high temperature 39 and as a metastable phase in instances of chemically exfoliated 18 and restacked 38 MX 2 monolayers.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…1. The 1T 0 phase is observed in WTe 2 under ambient conditions 17 , MoTe 2 at high temperature 39 and as a metastable phase in instances of chemically exfoliated 18 and restacked 38 MX 2 monolayers.…”
Section: Resultsmentioning
confidence: 97%
“…This polymorphism sets group VI TMD monolayers apart from other 2D materials such as graphene and hexagonal BN [17][18][19] . Intriguingly, one of these structural phases is semiconducting, whereas the others are metallic, unlike in the case of group V TMDs, where electrically activated metal-tometal structural phase transitions have been demonstrated in multilayer TaS 2 (ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined, it has early been observed that the n ‐butyllithium promoted exfoliation of MoS 2 , which involves also an ultrasonication step, leads also to the formation of defects (mainly described as sulfur vacancies) 19, 21b, 31a, 69. This on the other hand provided the basis for one of the initial covalent functionalization approaches for MoS 2 .…”
Section: Exploring the Chemistry Of Molybdenum Disulfidementioning
confidence: 99%